Strategy To Increase Regional Income In Takengon Through Local Culinary Development As A Destination Attraction Tour - Khairita Hasbi; Ismail, Ismail (SEAN Institute, 2024)
Tourism is one of the sectors that plays an important role in economic development. The current state of the tourism industry is growing rapidly, prompting various parties, from the government to the community, to make efforts to improve facilities and infrastructure to support tourism development, as it can have positive impacts on other sectors, especially in creating and expanding job opportunities. The aim of this research is to determine strategies for developing culinary tourism in Ujung Nunang tourist spot in Lut Tawar District, Central Aceh Regency, using ethnographic analysis, 4C, AHP, and SWOT. Interviews were conducted with informants to obtain information. Ethnographic analysis was used to identify three types of traditional foods in the Ujung Nunang tourist spot in Lut Tawar District, Central Aceh Regency, namely Masam Jing, Gutel, and Cecah Reraya Gayo. The attributes in the customer variable include visitor satisfaction, visitor loyalty, and how visitors obtain information. The attributes in the company variable include tourist attraction management, attraction, physical environment, company technology, and company services. The attributes in the changes variable include social culture, technology, law, politics, and economy. The attributes in the competitor variable include the number of competitors, advertising, customer service, price competitiveness, and technological competence. A strategy that needs to be implemented includes building a Culinary Tourism Village complete with food and beverages so that tourists can gather with their families on holidays. while enjoying the natural beauty and culture of Takengon, adding good photo spots while enjoying culinary tourism, improving access, upgrading facilities and infrastructure, enhancing the quality of dishes and adding the distinctive flavors of Takengon, and optimizing budget utilization